2017
DOI: 10.7213/academica.15.2017.05
|View full text |Cite
|
Sign up to set email alerts
|

Larvas de curimatã alimentadas com dietas em diferentes estados físicos

Abstract: Objetivou-se com o presente estudo verificar a influência dos diferentes estados físicos da ração nodesempenho de larvas de curimatã. Desenvolveu-se o experimento na Companhia de Desenvolvimento dosVales do São Francisco e Parnaíba (CODEVASF) de Três Marias/MG, por 21 dias. Larvas com quatro diasde vida e com peso médio inicial de 1,53 mg e comprimento médio total de 6,4 mm foram estocadas emuma densidade de 10 indivíduos L-1, em tanques com 10 L. Após a abertura da boca, estes peixes foramalimentados com náup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Several other authors have reported better zootechnical performance results for fish fed with extruded diets compared to press-pellet (Furuya, Souza, Furuya, Hayashi, & Ribeiro, 1998;Signor et al, 2011) and wet diets (Dias et al, 2017). Iglesias, Pérez, and de laVega (2007), when comparing a fish waste-based semi-moist diet with an extruded commercial diet for tilapia, did not obtain significant differences for FCR, survival and protein efficiency rate, however, higher final individual weights were observed.…”
Section: Discussionmentioning
confidence: 87%
“…Several other authors have reported better zootechnical performance results for fish fed with extruded diets compared to press-pellet (Furuya, Souza, Furuya, Hayashi, & Ribeiro, 1998;Signor et al, 2011) and wet diets (Dias et al, 2017). Iglesias, Pérez, and de laVega (2007), when comparing a fish waste-based semi-moist diet with an extruded commercial diet for tilapia, did not obtain significant differences for FCR, survival and protein efficiency rate, however, higher final individual weights were observed.…”
Section: Discussionmentioning
confidence: 87%